Elektroniczny łowca: postać cyborga w kinie science fiction głównego nurtu - Kamrowska, Agnieszka (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The aim of this text is to analyze the cyborg motif in mainstream American science fiction films, as represented by the Terminator and RoboCop film series. The cyborg characters presented in these films are focused mainly on violence and destruction, which emphasizes the technophobic attitude of the culture within which these films were made. The only redemption of their otherness is showing their humanity. For a cyborg, its technological provenance is a burden and results in its sense of guilt. In this manner, American science fiction films support anthropocentrism and the conservative status quo.